2022
DOI: 10.1111/jth.15881
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immunological anti‐platelet factor 4 antibodies for vaccine‐induced thrombotic thrombocytopenia (VITT) in a large Australian cohort: A multicenter study comprising 1284 patients

Abstract: Vaccine-induced (immune) thrombotic thrombocytopenia (VITT) is a rare complication of adenovirus-based vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which are aimed to prevent and minimize coronavirus disease 2019 and related pathophysiology. 1,2 Alternatively called thrombocytopenia with thrombosis syndrome (TTS) by government reporting agencies, such as the Therapeutic Goods Administration (TGA) in Australia, VITT affects 1 in 50 000 to 100 000 individuals vaccinated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…The study showed discrepancies in test results, highlighted the limitations of relying on a single method, and demonstrated the variability in phenotypes and pathomechanism of VITT. 30 Countries which have previously suspended the AstraZeneca COVID-19 vaccine include Denmark, Sweden, Italy, and Norway, among others. 31 ►Table 1 lists confirmed cases of VITT based on vaccine type.…”
Section: Incidence Of Vitt and Key Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…The study showed discrepancies in test results, highlighted the limitations of relying on a single method, and demonstrated the variability in phenotypes and pathomechanism of VITT. 30 Countries which have previously suspended the AstraZeneca COVID-19 vaccine include Denmark, Sweden, Italy, and Norway, among others. 31 ►Table 1 lists confirmed cases of VITT based on vaccine type.…”
Section: Incidence Of Vitt and Key Informationmentioning
confidence: 99%
“…1,37 Contrarily, the recent version for diagnosing VITT by the American Society of Hematology and THANZ use an inclusion criterion of 4 to 42 days, updated in May 2022 and December 2021, respectively, displaying the progression of understanding developed by the international community, as well as the cases attained in those localities. 3,30,36,39 The use of ELISA assays for detecting anti-PF4 antibodies has thus far been largely accepted to confirm VITT. 40,41 In terms of reporting, however, this criterion is not yet extensively indispensable.…”
Section: Diagnostic Criteria and Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition, called VITT, has been recently highlighted to occur following vaccination with some adenoviral-based COVID-19 vaccines, such as those manufactured by AstraZeneca (ChAdOx1-S/Vaxzevria) and Johnson & Johnson/Janssen (Ad26.COV2.S/Jcovden), which are otherwise aimed to reduce the incidence and morbidity of COVID-19 [ 65 ]. This condition may occur in approximately 1 in 50,000 doses of vaccine, and mimics HITT and HIT-like syndrome, since patients generate autoantibodies against PF4 that leads to platelet activation through Fc binding [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. However, the epitopes on PF4 to which the VITT antibodies bind are different to those in HITT and HIT-like syndrome, and whether the antibodies bind directly to PF4, or if there is an associated PF4 binding factor, is unknown.…”
Section: Autoimmune Disorders Leading To Thrombosismentioning
confidence: 99%